Enhancing Organizational Performance Through Knowledge Management In Saudi Arabia - M Banjer, Amro Ahmed (2010)
The sole purpose of this study was to explore the performance in Saudi organizations. Another purpose was to find the best strategy to enhance the performance. Both quantitative and qualitative methods were applied, quantitative in its questionnaire and qualitative in its interview and observation. This study investigated the workforce\'s understanding of knowledge management concepts and awareness of how to apply them, and explored organizational cultural issues, then evaluated the most efficient knowledge management processes and approaches for better performance.